Teaching and learning chemistry through the situational approach: Analysis and perspective, case of schools in Lubumbashi in the Democratic Republic of Congo. - Kasongo Nasser; Mutombo Hulumba.P; Kamand Yitil; Muleba Mvita .C (IJRDO- Journal of Educational Research, 2024)
The objective of this work was to verify the effectiveness of the practicability of the approach through situations in schools in this educational area. This study concerned 36 teachers who led the chemistry course in first scientific humanity and at the same time in the 8th basic education class, 180 students and parents of these students. After analyzing the data using the chi-square test and Fisher’s Z test, the set of results indicates the absence of chemistry equipment, the insufficiency of experimental practice by the students, there was question of the demonstration during some rare manipulations and the contributions of the situation-based approach were not found among the students. The multiplication of training in Approach through situations and the collaboration between teachers and artisans exploiting the notions of chemistry found in the learners’ environment for the contextualization of chemistry remain the strong points to be encouraged.